Integrated soil management for the dry savanna zone of West Africa: legume rotation and fertilizer N - Carsky, R.J.; Oyewole, B.; Tian, G. (1999)
Integrated soil management with leguminous cover crops was studied at two sites in the northern Guinea savanna zone of northern Nigeria, Kaduna (190 day growing season) and Bauchi (150 days). One-year planted fallows of mucuna, lablab, and crotalaria were compared with natural grass fallow and cowpea controls. All treatments were followed by a maize test crop in the second year with 0, 30, or 60 kg N ha−1 as urea. Above ground legume residues were not incorporated into the soil and most residues were burned early in the dry season at the Kaduna site. Legume rotation increased soil total N, maize growth in greenhouse pots, and dry matter and N accumulation of maize. Response of maize grain yield to 30 kg N ha−1 as urea was highly significant at both sites and much greater than the response to legume rotation. The mean N fertilizer replacement value from legume rotation was 14 kg N ha−1 at Kaduna and 6 kg N ha−1 at Bauchi. W ith no N applied to the maize test crop, maize grain yield following legume fallow was 365 kg ha−1 higher than natural fallow at Bauchi and 235 kg ha−1 higher at Kaduna. The benefit of specific legume fallows to subsequent maize was mostly related to above ground N of the previous legume at Bauchi, where residues were protected from fire and grazing. At Kaduna, where fallow vegetation was burned, maize yield was related to estimated below ground N. The results show that legume rotation alone results in small maize yield increases in the dry savanna zone.